2013
DOI: 10.1080/02699931.2013.867834
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias towards emotional facial expressions in survivors of dating violence

Abstract: This study identified components of attentional bias (e.g. attentional vigilance, attentional avoidance and difficulty with disengagement) that are critical characteristics of survivors of dating violence (DV). Eye movements were recorded to obtain accurate and continuous information regarding attention. DV survivors with high post-traumatic stress symptoms (DV-High PTSS group; n = 20) and low post-traumatic stress symptoms (DV-Low PTSS group; n = 22) and participants who had never experienced DV (NDV group; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 22 publications
7
46
4
Order By: Relevance
“…In Lee and Lee (2012) results indicated that increased dwell time on violent images in the high-PTSD group was relatively maintained throughout the 10-second trials (or the five 2-second intervals). In Lee and Lee (2014), similar results emerged with significant group differences in dwell time on angry and fearful faces maintained across time intervals. Thomas et al (2013) divided an overall presentation time of six seconds to three 2-seconds time intervals.…”
Section: Sustained Attention and Difficulty In Initial Disengagement supporting
confidence: 61%
See 4 more Smart Citations
“…In Lee and Lee (2012) results indicated that increased dwell time on violent images in the high-PTSD group was relatively maintained throughout the 10-second trials (or the five 2-second intervals). In Lee and Lee (2014), similar results emerged with significant group differences in dwell time on angry and fearful faces maintained across time intervals. Thomas et al (2013) divided an overall presentation time of six seconds to three 2-seconds time intervals.…”
Section: Sustained Attention and Difficulty In Initial Disengagement supporting
confidence: 61%
“…Four studies also incorporated general threat/negative stimuli in addition to trauma-specific stimuli to explore the level of threat specificity needed to elicit threat-related attention biases, which might reflect the generalization of these biases. Kimble et al (2010) used MVA pictures for Iraq war images, Thomas et al (2013) used general negative and general threat images in addition to the specific personal identified trauma images, Lee and Lee (2012) used dysphoric images in addition to the violent ones for DV victims, and Lee and Lee (2014) included fearful faces in addition to the angry faces, as only angry faces were considered trauma-relevant stimuli for DV survivors. Five studies included also positivevalence stimuli aiming to examine the emotionality hypothesis, namely, determine whether attention bias is manifested exclusively for threatening/negative information, or whether it may also be manifested when different valenced information is presented, such as positive stimuli.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations